1983
DOI: 10.1152/ajpcell.1983.245.1.c28
|View full text |Cite
|
Sign up to set email alerts
|

Actin filaments and vasopressin-stimulated water flow in toad urinary bladder

Abstract: Vasopressin increases the water permeability of the apical membrane of the granular epithelial cells of the toad urinary bladder. Cytochalasin B inhibits this action of the hormone, indicating that microfilaments may play a role in the water permeability response. We have extended previous functional studies with cytochalasin B and have demonstrated that dihydrocytochalasin B, a more specific inhibitor of actin filament elongation, similarly diminishes the hydrosmotic response to vasopressin. Biochemical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Previous studies using toad bladders have demonstrated the involvement of the F-actin cytoskeleton in AVP-mediated increases in osmotic water permeability (13,14). In addition, the reorganization of the F-actin cytoskeleton by AVP is a consistent finding in both amphibian urinary bladder epithelia and mammalian renal principal cells (2,16).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies using toad bladders have demonstrated the involvement of the F-actin cytoskeleton in AVP-mediated increases in osmotic water permeability (13,14). In addition, the reorganization of the F-actin cytoskeleton by AVP is a consistent finding in both amphibian urinary bladder epithelia and mammalian renal principal cells (2,16).…”
Section: Discussionmentioning
confidence: 74%
“…Microtubule-disrupting drugs like colchicine and nocodazole inhibit AVP-mediated increases in osmotic water permeability in renal collecting ducts by 65 and 72%, respectively (10 -13). Disruption of the F-actin cytoskeleton by cytochalasin B or dihydrocytochalasin B inhibits the AVP-induced increase in osmotic water permeability in toad bladder epithelium by 25-50% (13,14). The F-actin cytoskeleton also undergoes rearrangements after stimulation of cells with cAMP-elevating agents.…”
mentioning
confidence: 99%
“…Alternatively, vesicles containing ENaC could be trafficked or held in place by the cortical actin cytoskeleton. In the toad urinary bladder, the cortical actin cytoskeleton forms a meshwork of short filaments just under the apical surface when observed with an electron microscope (40); this is probably true for cortical collecting duct cells in the mammalian kidney. This would in turn lend support to previously reported observations that demonstrated that short actin filaments had an effect on ENaC by increasing the channel's open probability and decreasing its conductance (4,6).…”
Section: Discussionmentioning
confidence: 95%
“…In the case ofglucose transport, microfilament disruption with cytochalasin B resulted in impaired glucose transporter trafficking and diminished glucose uptake (50-53). Toad bladder studies have revealed that water transport is dependent upon water channel movement through the cytoskeleton, since water transport was inhibited after disruption of either microfilaments (54)(55)(56)(57) or microtubules (54,55,57). Although endocytosis through cytoskeletal domains appears to be required for a number of AP functions, there is little information about the role of the cytoskeleton in receptor-mediated signal transduction.…”
Section: Discussionmentioning
confidence: 99%